Factors associated with hypertension prevalence, unawareness and treatment among Costa Rican elderly - Santamaría-Ulloa Carolina; Méndez-Chacón Ericka; Rosero-Bixby Luis (BMC, 2008)
Abstract Background Reliable information on the prevalence of hypertension is crucial in the development of health policies for prevention, control, and early diagnosis of this condition. This study describes the prevalence of hypertension among Costa Rican elderly, and identifies co-factors associated with its prevalence, unawareness and treatment. Methods The prevalence of hypertension is estimated for the Costa Rican elderly. Measurement error is assessed, and factors associated with high blood pressure are explored. Data for this study came from a nationally representative sample of about 2,800 individuals from CRELES (Costa Rica: Longevity and Healthy Aging Study). Two blood pressure measures were collected using digital monitors. Self reports of previous diagnosis, and medications taken were also recorded as part of the study. Results No evidence of information bias was found among interviewers, or over time. Hypertension prevalence in elderly Costa Ricans was found to be 65% (Males = 60%, Females = 69%). Twenty-five percent of the studied population did not report previous diagnoses of hypertension, but according to our measurement they had high blood pressure. The proportion of unaware men is higher than the proportion of unaware women (32% vs. 20%). The main factors associated with hypertension are: age, being overweight or obese, and family history of hypertension. For men, current smokers are 3 times more likely to be unaware of their condition than non smokers. Both men and women are less likely to be unaware of their condition if they have a family history of hypertension. Those women who are obese, diabetic, have suffered heart disease or stroke, or have been home visited by community health workers are less likely to be unaware of their hypertension. The odds of being treated are higher in educated individuals, those with a family history of hypertension, elderly with diabetes or those who have had heart disease. Conclusion Sex differences in terms of hypertension prevalence, unawareness, and treatment in elderly people have been found. Despite national programs for hypertension detection and education, unawareness of hypertension remains high, particularly among elderly men. Modifiable factors identified to be associated with prevalence such as obesity and alcohol intake could be used in educational programs aimed at the detection and treatment of those individuals who have the condition.